GLP-1 receptor agonist use does not increase risk of respiratory complications post-endoscopy - Velji-Ibrahim, Jena; Nathani, Piyush; Patel, Harsh K; Sharma, Prateek (Endoscopy International Open, 2025)
Data on respiratory complications associated with GLP-1 receptor agonist (GLP-1 RA) use before endoscopic procedures are limited.We conducted a retrospective cohort study using TriNetX in adults with diabetes or obesity on GLP-1 RAs within 3 months of endoscopy, comparing them with non-GLP-1 RA users. Propensity score matching and Cox proportional hazards models were used to assess outcomes.Among 46,948 patients, no significant differences in post-endoscopy aspiration pneumonitis (hazard ratio [HR] 0.92, 95% confidence interval [CI] 0.54–1.56) or pneumonia (HR 1.01, 95% CI 0.83–1.24) were found between groups.GLP-1 RA use before endoscopy does not increase respiratory complications, supporting continued preoperative medication use.
Keywords: Quality and logistical aspects; Performance and complications; Preparation; Endoscopy Upper GI Tract; Endoscopy Lower GI Tract